Application of experience of England tourism brand promotion in terms of innovative development of Kazakhstan - Kairova, A.A.; Esimzhanova, S.R. (BUKETOV BUSINESS REVIEW, 2017)
In this study, we analyzed the UK experience in promoting national tourism brand. The relevance of the problem caused by the need to implement the best technologies in the creation and promotion of tourism brand in Kazakhstan in terms of innovative formation of the country and the activity of competitor countries. In our view, the UK experience in the application of integrated and sustainable approach to the management of the national tourism brand is effective for the growth of domestic tourism in Kazakhstan. Learning and transformation experience of developed countries has become a necessity in the conditions of an active and continuous struggle for a place in the highly competitive global tourism market. Formation of high quality Kazakhstan tourist world-class product, development of the idea of travel among the Kazakhs in the own country, the creation of a specialized organization such as VisitEngland engaged in carrying out marketing activities; cooperation of the state with a variety of public and private companies; support funds for the development of national and business travel, and most importantly, matching the expectations of local and foreign tourists to the real content of the tourism brand that will allow Kazakhstan to become a strong brand. In turn, a strong tourist country brand — It is a globally recognized Kazakhstan in world tourism space.